Students’ Literacy and Articles’ Quality Improvement in the Faculty of Da’wa and Communication in Sunan Kalijaga State Islamic University - Syamsiyatun, Siti; Izudin, Ahmad (LENTERA, 2021)
The aim of this article is to investigate student interest in accessing online platform of academic journals in the Faculty of Da’wah and Communication, UIN Sunan Kalijaga, Yogyakarta. This research applied survey method with quantitative technique to analyse collected data. The results show that all variables tested by conclusions are accepted. This means, after processing the data from the results of questionnaires, it can be seen that the data tested with simple linear regression methods have a positive value so it shows that students’ interest in accessing online journal has an effect on improving quality of their articles. Meanwhile, student interest in accessing online journal survey was still minimal, with 42.2% answered that they do not know the existence of the academic journals. However, 98% of students answered that the internet is a primary need. Unfortunately, the internet, as a tool to access online journals, is mostly used to find entertainment contents with a percentage of 56%. This value is obtained from the average access to the internet; 38% in between 1-3 hours, 30.4% in between 4-6 hours, 22.8% in between 7-10 hours, 4.8% in between 11-13%, ad 4% in > 14 hours.Keywords: Online academic journals, student interest, and survey.